Bone mineral response to physical activity and sport practice - Filho, Dalton M. Pessôa [UNESP]; Massini, Danilo A. [UNESP]; Macedo, Anderson G. [UNESP]; Vasconcelos, Camila M.T. [UNESP]; Oliveira, Thiago P. [UNESP]; dos Santos, Luiz Gustavo Almeida [UNESP] (My University, 2021)
Bone mineral density and content are measurements of the structural quality of bone hard tissue. These variables are used to access the bone health status. The fact that bone mineral density and content reduce with aging, physical inactivity, menopause/andropause, obesity, and diabetes, allows to presume that bone frailty is related to metabolic and motor disturbances, impairing quality of life. However, the tensional stimulus of muscle contraction and the magnitude of body muscle mass are mechanical factors that affect bone metabolism by increasing osteoblastic activity among adults of different age, gender and ethnicity. In fact, exercise performed with moderate to high-intensity motor demand produces autocrine, paracrine, and endocrine adjustments that modulate muscle energy metabolism, myofibrils synthesis, and bone osteogenic signalization. Indeed, if such type of physical exercise practice includes bone-bearing actions, it is expected that it can provide the stimulus to remodel bone tissue, which accounts for the higher whole-body or regional bone mineral density and content among athletes when compared to their sedentary peers. However, swimming practice has no similar effect on bone mineral density and content as that observed for weight-bearing sports activities. Instead, the osteogenic metabolism of swimmers is neither positively nor negatively affected by the mechanical and physiological loads during swimming practice, as likely seems to be the case of healthy non-athletes. This chapter aims to describe the fundamentals of the causeeffect relationship between the patterns of mechanical stimulation, according to different sports practices, as well as to analyze how the changes in lean mass and muscle strength of athletes contribute to bone adjustments according to age and gender. Collectively, the analyzed studies showed that muscular strength is likely to be an index of bone mineral integrity (influencing directly and indirectly-through lean body mass-bone mineral density and content). The analyzed studies also showed that mechanical stimuli (impact or/and muscle tension), mostly provided by sports and physical activities in a terrestrial environment, tend to stimulate a high effect on bone mineral density at the hip, femur, pelvis, lumbar spine and whole-body. This effect on different anatomical sites is higher than that from low-impact sports (such as swimming), as well as when compared to elderly and sedentary individuals. Thus, the development of muscular strength is repeatedly important for the maintenance of bone health in young, adults, and elderly people.
Keywords: Age groups; Bone frailty; Bone mineral mass; Exercise; Gender; Healthy lifestyle